Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1016/j.neuron.2005.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Protein Synthesis-Independent Plasticity Mediates Rapid and Precise Recovery of Deprived Eye Responses

Abstract: Monocular deprivation (MD) for a few days during a critical period of development leads to loss of cortical responses to stimulation of the deprived eye. Despite the profound effects of MD on cortical function, optical imaging of intrinsic signals and single-unit recordings revealed that deprived eye responses and orientation selectivity recovered a few hours after restoration of normal binocular vision. Moreover, recovery of deprived eye responses was not dependent upon mRNA translation, but required cortical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 52 publications
2
30
0
Order By: Relevance
“…Furthermore, H-ras G12V expression is unique in accelerating both deprivation-induced plasticity and recovery from deprivation. Previous studies have shown that these two processes differ mechanistically, involving distinct cellular processes (8,30,31). H-ras is known to initiate signaling pathways leading to activation of distinct sets of effector molecules depending on cellular conditions (15), consistent with our finding that constitutive activation of H-ras affects plasticity both during MD and during recovery from deprivation.…”
Section: Discussion Acceleration Of Multiple Forms Of Visual Cortex Psupporting
confidence: 90%
“…Furthermore, H-ras G12V expression is unique in accelerating both deprivation-induced plasticity and recovery from deprivation. Previous studies have shown that these two processes differ mechanistically, involving distinct cellular processes (8,30,31). H-ras is known to initiate signaling pathways leading to activation of distinct sets of effector molecules depending on cellular conditions (15), consistent with our finding that constitutive activation of H-ras affects plasticity both during MD and during recovery from deprivation.…”
Section: Discussion Acceleration Of Multiple Forms Of Visual Cortex Psupporting
confidence: 90%
“…Optical imaging of intrinsic signals was performed with Imager 2001 VSDϩ (Optical Imaging System, Germantown, NY) by using imaging methods slightly modified from those described previously (Medina et al, 2003;Krahe et al, 2005). Briefly, animals were premedicated, anesthetized, and ventilated with similar procedures described for single-unit recordings.…”
Section: Methodsmentioning
confidence: 99%
“…The approximate location of the border between V1 and V2 was still distinguishable after 3 d of monocular deprivation (MD). However, longer periods of MD lead to saturating left eye dominance in V1/V2, making this distinction more difficult (Krahe et al, 2005). After defining the ROI, we created ocular dominance histograms based on the range of gray values (0 -255) divided into five class intervals, where 0 -50 and 204 -255 correspond to classes containing the darkest and lightest pixels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…A number of studies show that ipsilateral eye pathways are differentially affected by monocular deprivation (Antonini et al 1999;Krahe et al 2005;Tagawa et al 2005). In light of these studies, we examined the effects of visual manipulation on ipsilateral eye cortical maps.…”
Section: Plasticity Of Ipsilateral Eye Mapsmentioning
confidence: 99%